1963
DOI: 10.1128/jb.85.4.932-939.1963
|View full text |Cite
|
Sign up to set email alerts
|

MORPHOLOGY OF TREPONEMA MICRODENTIUM AS REVEALED BY ELECTRON MICROSCOPY OF ULTRATHIN SECTIONS

Abstract: Broth cultures of a strain of Treponema microdentium were harvested on Millipore filters, fixed in osmic acid, and sectioned for electron microscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
16
0

Year Published

1964
1964
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 15 publications
5
16
0
Order By: Relevance
“…Listgarten et al demonstrated that the axial fibrils of Treponema microdentium were situated between the external envelope and the protoplasmic cylinder when viewed in thin sections. They further showed that the "granule," which seemed to be morphologically identical with our SB, had a membrane or an outer envelope surrounding axial fibrils and the protoplasmic cylinder (15). The continuation of the limiting membrane of the spherical structure with the outer envelope of the spirochete was confirmed by other investigations on Treponema (3,5,13,18).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Listgarten et al demonstrated that the axial fibrils of Treponema microdentium were situated between the external envelope and the protoplasmic cylinder when viewed in thin sections. They further showed that the "granule," which seemed to be morphologically identical with our SB, had a membrane or an outer envelope surrounding axial fibrils and the protoplasmic cylinder (15). The continuation of the limiting membrane of the spherical structure with the outer envelope of the spirochete was confirmed by other investigations on Treponema (3,5,13,18).…”
Section: Discussionsupporting
confidence: 83%
“…Several investigators have studied these structures by electron microscopy and have discussed their significance (6,8). With a few exceptions (3,15), the information on human oral treponemes has been obtained from negatively stained or shadowed preparations.In a previous paper (21), we reported that the spherical body (SB) of oral spirochetes differed in size and formation rate from those observed by Hampp (7) and that the SB had a great affinity for oral spiroch etal cells. Because of its large size, our oral spirochete provided a model for studying the fine structure and biological characteristics of the SB.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Spirochetes are well known to be microorganisms forming morphologically abnormal structures both in vitro and in vivo. Under certain conditions these abnormal structures observed by electron microscopy have been shown to be the result of outerward expansion and/or development of the capsule as a limiting membrane which surrounds the axial flagella and main bodies of the organisms (1, 3,6).…”
mentioning
confidence: 99%
“…Helical cells of T. phagedenis biotype Reiter are converted into spherical forms by exposure to hypotonic conditions upon separation of the outer sheath from the protoplasmic cylinder (2). Similar spherical conversion of spirochetal cells is also found during the stationary growth phase of spirochetes (5,7). The conversion of helical cells into the spherical form may be caused by disintegration of the connective fibrils between the outer sheath and the wall-membrane complex followed by expansion of the outer sheath, because the protoplasmic cylinder still maintains a helical shape within the sperical form (1,7,11).…”
mentioning
confidence: 66%